1998
DOI: 10.1136/fn.79.1.f26
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of early postnatal dexamethasone for prevention of chronic lung disease

Abstract: Aim-To review systematically the evidence to determine whether dexamethasone treatment of very low birthweight infants begun within 14 days of age prevents chronic lung disease (CLD) without clinically significant side eVects. Methods-Randomised controlled trials of dexamethasone started within this time frame were identified through a search of electronic databases, proceedings of scientific meetings, and personal files. Metaanalyses using event rate ratio (ERR), event rate diVerence (ERD), and if significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 35 publications
(51 reference statements)
2
80
0
Order By: Relevance
“…5,6 Metaanalyses of early (Ͻ96 hours of age) 7 and later use of PNSs to reduce CLD 8,9 demonstrated significant benefits with regard to earlier extubation and decreased risks of CLD at both 28 days and 36 weeks, death, or CLD at 28 days and 36 weeks, but there was a disturbing tendency toward an increase in neurodevelopmental impairment consistent with previous animal experiments, which had shown that glucocorticoids administered during critical periods of brain development may impair myelinization, brain cell division, and longer-term behavioral effects. [10][11][12][13][14][15][16] The American Academy of Pediatrics Committee on the Fetus and Newborn cautioned that PNS use outside of randomized trials should be reserved for "exceptional clinical circumstances."…”
Section: Authorsmentioning
confidence: 99%
“…5,6 Metaanalyses of early (Ͻ96 hours of age) 7 and later use of PNSs to reduce CLD 8,9 demonstrated significant benefits with regard to earlier extubation and decreased risks of CLD at both 28 days and 36 weeks, death, or CLD at 28 days and 36 weeks, but there was a disturbing tendency toward an increase in neurodevelopmental impairment consistent with previous animal experiments, which had shown that glucocorticoids administered during critical periods of brain development may impair myelinization, brain cell division, and longer-term behavioral effects. [10][11][12][13][14][15][16] The American Academy of Pediatrics Committee on the Fetus and Newborn cautioned that PNS use outside of randomized trials should be reserved for "exceptional clinical circumstances."…”
Section: Authorsmentioning
confidence: 99%
“…In the past decade, there has been a significant increase in the use of glucocorticoids (particularly i.v. dexamethasone) in the NICU (17,18), and this practice is coincident with the increase in C. albicans infections (7,19). Although dramatic physiologic improvement in pulmonary function can been seen almost immediately with the use of steroids in premature infants, both short-term and long-term adverse affects, including increased risk of infection, are now being documented [(20), also reviewed by Jobe (21)].…”
mentioning
confidence: 99%
“…Over the past decades, methods have differed as to the beginning of administration of corticosteroids: (i) from the first hours of life (early), 6,[7][8][9]16,[45][46][47] (ii) from 7 to 14 days of life (moderately early), 12,23,48 (iii) after 14 days of life (late) 10,13,49,50 . Doses and the length of treatment (from 9 to 42 days) are also reported.…”
Section: Discussionmentioning
confidence: 99%